Enterprise operating system framework: federated interoperability based on HLA. (2018) - Youssef, Joseph Rahme; Zacharewicz, Gregory; Chen, David; Tu, Zhiying
Operating system (OS) is a well-known concept in computer science as an interface between human and computer hardware (MacOS, Windows, IOS, Android). In the perspective of developing future generation of enterprise systems based on IoT and cyber-physical system principles, this paper proposes to develop an enterprise operating system (EOS) that will act as an interface between enterprise business managers and enterprise resources performing enterprise operations. The paper presents at first a set of requirements and functionalities of EOS. Then a survey on existing relevant works is given and mapped to the requirements. After that the existing models related to the federated enterprise interoperability are presented. The architectures of envisioned EOS and the federated interoperability are outlined. The last part draws some conclusions and gives future perspectives.